The relationship between malnutrition, diet quality and health-related quality of life among the elderly: A cross-sectional study - Gezer, Ceren; Yurt , Merve; Harmancıoğlu, Begüm; Yıldırım, Ayşen; Elmas, Cemre (Progress in Nutrition, 2021)
Introduction: This study aims to evaluate the relationship between malnutrition, diet quality and health-related quality of life among the elderly in Famagusta, Cyprus.Materials and Methods: This study was conducted with 279 individuals aged 65 and over who were living in Famagusta, Cyprus between February 2017 and May 2018. Data was collected via one-to-one interviews using the following evaluation forms. The Mini Nutritional Assessment (MNA) evaluated demographic characteristics, nutritional habits, 24-hour retrospective food consumption records and risk of malnutrition. The Medical Outcome Study Short Form (SF-36) evaluated quality of life. In addition, participants’ body weight, height, waist, hip, mid-upper arm and calf circumferences were measured using appropriate techniques.Results: Of the participants, 5.4% had malnutrition, and 9.3% were at risk of malnutrition. Participants over the age of 85 had the highest risk of malnutrition (p